The proceedings of the Special Offshore Symposium China, held at Beijing, China, 16-18 April 1994 - Special Offshore Symposium China (1994 : Beijing, China); Li, Yu-cheng; Chung, Jin S.; International Society of Offshore and Polar Engineers (Golden, Colo. : ISOPE, 1994)
07